Potential Impact on Spatial Access to Surgery Under a Low Volume Pledge: A Population-Level Analysis of Patients Undergoing Pancreatectomy - Fong, Zhi Ven (Surgery, 2017)
BACKGROUND: A minimum-volume policy restricting hospitals not meeting the threshold from performing complex surgery may increase travel burden and decrease spatial access to surgery. We aim to identify vulnerable populations that would be sensitive to an added travel burden. METHODS: We performed a retrospective analysis of the California Office of Statewide Health Planning and Development database for patients undergoing pancreatectomy from 2005 to 2014. Number of hospitals bypassed was used as a metric for travel. Patients bypassing fewer hospitals were deemed to be more sensitive to an added travel burden. RESULTS: There were 13,374 patients who underwent a pancreatectomy, of which 2,368 (17.7%) were non-bypassers. On unadjusted analysis, patients >80 year old travelled less than their younger counterparts, bypassing a mean of 10.9 ± 9.5 hospitals compared to 14.2 ± 21.3 hospitals bypassed by the 35–49 year old age group (p<0.001). Racial minorities travelled less when compared to Non-Hispanic Whites (p<0.001). Patients identifying their payer status as self-pay (8.9 ± 15.6 hospitals bypassed) and Medicaid (10.1 ± 17.2 hospitals bypassed) also travelled less when compared to patients with private insurance (13.8 ± 20.4 hospitals bypassed, p<0.001). On multivariate analysis, advanced age, racial minority and patients with self-pay or Medicaid payer status were independently associated with increased sensitivity to an added travel burden. CONCLUSION: In patients undergoing pancreatectomy, the elderly, racial minorities and patients with self-pay or Medicaid payer status were associated with an increased sensitivity to an added travel burden. This vulnerable cohort may be disproportionately affected by a minimum-volume policy.